Soil Carbon Sequestration under Different Agroforestry Land Use Systems - Khaki, Bilal Ali; Wani, Akhlaq Amin; Bhardwaj, D. R.; Singh, V. R. R. (Indian Forester, 2016)
Trees are known to maintain soil organic matter and nutrient cycling through the addition of litter and root residues into the soil. There is a large potential of sequestering carbon in soil and vegetation by adopting suitable agroforestry systems. The present investigation was conducted during January-June 2007 at Poanta valley of Himachal Pradesh, located at an elevation of 350 m amsl. Six agroforestry systems were selected viz. hortipastoral system (HP) (Mango + natural grasses), silvi-pastoral system (SP) (Dalbergia sissoo+ natural grasses), agri- silviculture system (AS) (Sal + wheat), horti-silvipastoral (HSP) (Mango+ Poplar + natural grasses), Pure Forest (F) (Sal), natural grass land (NG) (pure grasses). At 0-20 cm depth, soils under natural grassland was having higher bulk density (1.28g cm-3 ) among all the systems while lowest bulk density (1.16 g cm-3 ) was observed under forest. In 20-40 cm depth, the results also showed significant variation at 5% level of significance. Soil organic carbon (SOC) at the soil depth 0-20 cm was highest under forest (3.64 %) while silvi-pastoral system showed the lowest (1.30 %). In general, SOC pool in the 0-20 cm layer was quite higher than that of 20-40 cm layer. The total SOC pool for different Agroforestry system followed the decreasing order as PF (1373.7 Mg ha-1) > HSP (719.6 Mg ha-1) > AS (697.3 Mg ha-1) > NG (696.5 Mg ha-1) > HP (646 Mg ha-1) > SP (599.10 Mg ha-1).